MIKROZONASI DAERAH KENDARI DAN SEKITARNYA BERDASARKAN RESPONS TANAH SETEMPAT - Marjiyono, Marjiyono; Soehaimi, Asdani; H. Setiawan, J. (Jurnal Geologi dan Sumberdaya Mineral, 2007)
As one of the provincial capital city which is growing  fast, database of earth sciences is absolutely required In order to develop the secure of Kendari town. Measurement   of microtremor   in this region aims  to know the site response forward ground shacking. The result of microtremor analysis indicates that the distribution of dominant period of H/V ratio of Kendari and its surrounding area is parallel to Kendari bay, and turning south to follow the pattern of Wanggu river. Susceptibility  level in this area which  is represented by dominant period values is divided  into four categories (> 1.5 seconds, 1.5  -1.0 seconds, 1.0- 0.5 seconds, and <0.5 second). Generally, the pronest area coinciding with recent sedimentation  area, is around  Kendari  Bay and along Wanggu river, while towards outside are it is safer. Keyword:microtremor, ground shacking, Kendari